2016
DOI: 10.3847/0004-6256/151/3/76
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble Empirical Mode Decomposition of the Magnetic Field of the Sun as a Star

Abstract: The ensemble empirical mode decomposition (EEMD) analysis is utilized to extract the intrinsic mode functions (IMFs) of the solar mean magnetic field (SMMF) observed at the Wilcox Solar Observatory of Stanford University from 1975 to 2014, and then we analyze the periods of these IMFs as well as the relation of IMFs (SMMF) with some solar activity indices. The two special rotation cycles of 26.6 and 28.5 days should be derived from different magnetic flux elements in the SMMF. The rotation cycle of the weak ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…The EMD (and EEMD, CEEMDAN) method does not require a priori assumption about the signal type, therefore it is widely and successfully used in the analysis of non-linear and non-stationary real-world signals, such as the variability of total solar irradiance (Li et al 2012;Lee et al 2015), the periodicity of flare index (Gao et al 2011), the research of solar mean magnetic field (Xiang & Qu 2016), the sunspot numbers (Barnhart & Eichinger 2011), etc (either EMD or EEMD is used in these studies). This method is more effective than the traditional Fourier analysis in extracting modes with time-variable amplitudes and timevarying frequencies in signals.…”
Section: Complete Ensemble Empirical Modementioning
confidence: 99%
“…The EMD (and EEMD, CEEMDAN) method does not require a priori assumption about the signal type, therefore it is widely and successfully used in the analysis of non-linear and non-stationary real-world signals, such as the variability of total solar irradiance (Li et al 2012;Lee et al 2015), the periodicity of flare index (Gao et al 2011), the research of solar mean magnetic field (Xiang & Qu 2016), the sunspot numbers (Barnhart & Eichinger 2011), etc (either EMD or EEMD is used in these studies). This method is more effective than the traditional Fourier analysis in extracting modes with time-variable amplitudes and timevarying frequencies in signals.…”
Section: Complete Ensemble Empirical Modementioning
confidence: 99%
“…Previous studies showed that there is a general consensus on ⋆ E-mail: fengwang@gzhu.edu.cn (FW) the magnitude and form of the interior rotation as inferred from helioseismology (Antia et al 1998), the surface differential rotation rate as derived from sunspots (Javaraiah 2013), Doppler velocity measurements (Snodgrass & Ulrich 1990), as well as the magnetic activity features (Komm et al 1993;Xiang & Qu 2016), but there is no such consensus regarding the rotation rule for the features in the solar corona, as pointed out by Hiremath & Hegde (2013). The main reasons why the coronal rotation is relatively less determined are as follows: i) there are virtually no obvious tracers, ii) the corona is the optically thin region, and iii) it is difficult to measure the coronal magnetic field (Vats et al 1998;Bhatt et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A huge amount of free magnetic energy stored in the solar atmosphere is released during their eruptions (Forbes 2000;Priest & Forbes 2002;Schmieder et al 2015). This energy is transformed into radiative energy, bulk kinetic energy, as well as thermal and nonthermal energy (Deng et al 2013;Lin et al 2015;Xiang & Qu 2016).…”
Section: Introductionmentioning
confidence: 99%